Self-Accessible States for Linear Systems on Time Scales - Henriquez-Miranda, H (American Mathematical Society, 2018)
In this paper, we are concerned with linear control systems on time scales. We show that, under appropriate hypotheses, the self-accessible trajectories have diameter greater than or equal to a certain fixed positive number. © 2017 American Mathematical Society.